Case report: Anti septin-5-encephalitis as a treatable cause of cerebellar ataxia and psychiatric symptoms - Wischmann, Johannes; Borowski, Kathrin; Havla, Joachim; Thaler, Franziska S.; Winkler, Tobias; Jung, Tobias; Straube, Andreas; Masouris, Ilias (Frontiers in Neurology, 2023)
Objectives Anti-septin-5 encephalitis is a rare disease with only few published cases, mainly based on retrospective CSF and serum analyses. Predominant symptoms are cerebellar ataxia and oculomotor abnormalities. Due to the rareness of the disease, treatment recommendations are scarce. Herein, we prospectively describe the clinical course of a female patient with anti-septin-5 encephalitis. Methods We describe diagnostic workup, treatment and follow-up of a 54-year-old patient presenting with vertigo, unsteady gait, lack of drive and behavioral changes. Results Clinical examination revealed severe cerebellar ataxia, saccadic smooth pursuit, upbeat-nystagmus, and dysarthria. Additionally, the patient presented with a depressive syndrome. MRI of the brain and spinal cord were normal. CSF analysis showed lymphocytic pleocytosis (11 cells/μl). Extensive antibody testing revealed anti septin-5 IgG in both CSF and serum without coexisting anti-neuronal antibodies. PET/CT detected no signs of malignancy. Corticosteroids, plasma exchange, and rituximab led to transient clinical improvement followed by relapse. Re-applied treatment with plasma exchange followed by bortezomib resulted in moderate but sustained clinical improvement. Discussion Anti septin-5 encephalitis represents a rare but treatable and therefore relevant differential diagnosis in patients with cerebellar ataxia. Psychiatric symptoms can be observed in anti septin-5 encephalitis. Immunosuppressive treatment including bortezomib is moderately effective.